Otoritas Keagamaan di Era Media Baru: Dakwah Gusmus di Media Sosial - Arnis Rachmadhani (LP2M UIN Sunan Kalijaga, 2021)
This article examines religious authority and new media, with a case study on Gus Mus' da'wah model. The research question of this research is how the authority of religious sources changes from the analog to digital era; how is the map of the authority of traditional religious sources in the era of disruption; and how is the strategies of traditional religious source authorities in the era of new media. To answer this question, this study combines ethnographic and netnographic data. Ethnographic data was carried out through interviews and following Gus Mus' da'wah activities on several social media. Meanwhile, netnographic data was carried out by searching online data and observing online participants. The results of this study indicate that the presence of social media as a form of new da'wah model does not shift traditional religious authority, but instead strengthen this authority. Thanks to the social media. Traditional Islam would always become the authoritative source of public religious understanding. Therefore, new religious authorities or known as charismatic dai also come from the circle of dais who have a formal Islamic education background or pesantren which comprehend the pesantren classical books and other Islamic religious sciences. Gus Mus, who was originally a traditional religious authority, massively disseminated his da'wah to online spaces, especially Instagram, YouTube, Facebook, Podcasts, and WhatsApp. Therefore, Gus Mus' authority as a preacher persisted and even strengthened, thanks to the charismatic clerical culture that was obtained from the new media. Finally, thanks to the combination of traditional culture and the role of new media, Gus Mus' charisma is distinguishing and different from other new religious authorities. Thanks to the support of his media team, his religious universal message can be more widely spread in every level of society. [Artikel ini mengkaji tentang otoritas keagamaan dan media baru, dengan studi kasus pada model dakwah Gus Mus. Pertanyaan yang diajukan adalah bagaimana pergeseran otoritas sumber keagamaan dari era analog ke digital?; bagaimana peta otoritas sumber keagamaan tradisional di era disrupsi?; dan bagaimana strategi otoritas sumber keagamaan tradisional di era media baru? Untuk menjawab pertanyaan tersebut, penelitian ini mengkombinasikan data etnografi dan netnografi. Data etnografi dilakukan melalui wawancara dan mengikuti kegiatan dakwah Gus Mus di beberapa media sosial. Sedangkan data netnografi dilakukan melalui penelusuran data-data online dan observasi partisipan online. Hasil penelitian ini menunjukkan bahwa kehadiran media sosial sebagai bentuk model dakwah baru tidak menggeser pengaruh otoritas keagamaan tradisional, tetapi justru semakin memperkuatnya. Berkat media sosial, Islam tradisional tetap menjadi sumber otoritatif pemahaman keagamaan mayoritas umat. Oleh karena itu, figur otoritas Islam tetap berasal dari lingkaran dai yang memiliki latar belakang pendidikan Islam formal ataupun pesantren yang menguasai kitab-kitab klasik (turath) pesantren dan menguasai ilmu-ilmu agama Islam lainnya. Sebagai figur otoritatif keagamaan tradisional, Gus Mus secara masif mendiseminasikan dakwahnya ke ruang online, utamanya Instagram, YouTube, Facebook, Podcasts, maupun WhatsApp. Oleh karena itu, otoritas Gus Mus sebagai seorang dai tetap bertahan dan bahkan menguat berkat media baru. Berkat perpaduan antara kultur tradisional dan peran media baru, Gus Mus tampil sebagai figur karismatik otoritas Islam tradisional yang khas dan berbeda dari figur otoritas keagamaan baru lainnya. Berkat dukungan tim medianya, pesan universal dakwahnya dapat lebih luas tersebar ke setiap lapisan masyrakat.]